Pengaruh Harga dan Kualitas Pelayanan terhadap Loyalitas Pelanggan pada Bookstore Rumah Sita Sangatta - Nor Khafizah; Imrona Hayati; Ulfa Jamilatul Farida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine how price and service quality affect customer loyalty in buying books at Rumah Sita Sangatta Bookstore. This type of research is field research using a quantitative approach. This study uses data collection techniques, namely questionnaire techniques to obtain research data, then observation techniques, then documentation techniques. The population in this study was 120 respondents and a sample of 30. Quota sampling technique was used by selecting respondents. Data analysis was carried out using multiple linear regression analysis and obtained the equation Y = 2.612 + 0.224 (X₁) + 0.348 (X₂), the results indicate that price and service quality (X₂) have a positive and significant effect on customer loyalty (Y). The results of the partial t-test showed that price had a positive and significant effect on customer loyalty (t count 2.184> t table 2.051; sig. 0.036 <0.05). Service quality (X₂) has a positive and significant effect (t count 2.250 > t table 2.051; sig. 0.031 < 0.05). Simultaneous f test, both independent variables have a positive and significant effect on the dependent variable (F count 16.152 > F table 3.34; sig. 0.000 < 0.05). The coefficient of determination (R²) value of 0.485 indicates that 49% of the variation in customer loyalty is explained by pricing and service quality, while the remaining 51% is influenced by other variables that the researcher did not examine.